(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Banking industry has been in a process of significant transformation. The transformation in the banking industry is based on innovation in information technology. Information communication technology is the backbone of global change curve by internet banking in Nigeria. It is against this background that the study examined the relationship of internet banking on performance of banks. (A case study of Deposit Money Banks in Nigeria). Using time series data of 2011 – 2015, the study employed regression technique in the analysis of sourced data. Data were collected from secondary sources through annual reports and statistical bulleting of central bank of Nigeria. Internet banking was measured using the total value of internet and mobile banking while Bank performance was measured using return on total assets and return on equity of deposit money banks in Nigeria. Return on equity was regressed on internet and mobile banking, and return on total assets was also regressed on internet and mobile banking using multiple regression technique. The study revealed that positive relationship exists between mobile banking and return on equity, and between internet banking and return on assets. While on the other hand no significant relationship between internet banking and return on equity, and between mobile banking and return on assets. It is therefore, recommended that banks must offer numerous services through mobile banking Banks and effective transaction through the internet.